Treatment Outcomes of Systemic Therapies for Infiltrative Hepatocellular Carcinoma - Chen PY; Chang CK; Chen BB; Hsu CH; Cheng AL; Shao YY (Journal of Hepatocellular Carcinoma)
Po-Yi Chen,1,2 Chih-Kai Chang,3 Bang-Bin Chen,3 Chih-Hung Hsu,1,2,4 Ann-Lii Cheng,1,2,4 Yu-Yun Shao1,2,4 1Department of Medical Oncology, National Taiwan University Cancer Center, Taipei, Taiwan; 2Department of Oncology, National Taiwan University Hospital, Taipei, Taiwan; 3Department of Medical Imaging, National Taiwan University Hospital, Taipei, Taiwan; 4Graduate Institute of Oncology, College of Medicine, National Taiwan University, Taipei, TaiwanCorrespondence: Yu-Yun Shao, Department of Oncology, National Taiwan University Hospital, 7 Chung-Shan South Road, Taipei, 10002, Taiwan, Tel +886 2 23123456 ext. 266008, Fax +886 2 23711174, Email yuyunshao@gmail.comPurpose: Outcomes in the treatment of unresectable infiltrative hepatocellular carcinoma (HCC) are poorly understood, and infiltrative HCC is generally underrepresented in clinical trials. The present study explored outcomes associated with the treatment of infiltrative HCC with various systemic therapies.Patients and Methods: We enrolled all patients with Barcelona Clinic Liver Cancer stage C infiltrative or multinodular HCC who received first-line systemic therapy between January 2015 and December 2021 at a single center. We compared baseline characteristics and treatment outcomes for the two HCC subtypes.Results: In total, 260 patients were enrolled, 128 (49.2%) of whom had infiltrative HCC. Patients with infiltrative HCC were more likely to have macrovascular invasion (91.4% vs 68.2%, p < 0.001) but less likely to have extrahepatic spread (32.0% vs 54.5%, p < 0.001) than patients with multinodular HCC. In patients who received multikinase inhibitors alone, the time to treatment failure (TTF) and overall survival (OS) were similar for the 2 HCC subtypes. In patients who received immune checkpoint inhibitor (ICI)-based therapy, multivariate analyses revealed that infiltrative HCC was associated with shorter TTF (HR: 4.07, 95% CI: 2.13– 7.79, p < 0.001) and poorer OS (HR: 3.27, 95% CI: 1.76– 6.11, p < 0.001).Conclusion: In patients receiving ICI-based therapy for HCC, infiltrative HCC was associated with poorer outcomes.Keywords: hepatocellular carcinoma, HCC, infiltrative, systemic therapy, multikinase inhibitor, immune checkpoint-inhibitor